Unusual Neuroimaging in a Case of Rapidly Progressive Juvenile-Onset Krabbe Disease. (September 2020) - Kripps, Kimberly; Kierstein, Janell; Nicklas, Daniel; Nelson, Julie; Yang, Michele; Collins, Abigail; Troy, Elizabeth; Escolar, Maria; Maloney, John; Neuberger, Ilana; Stence, Nicholas; Baker, Peter R.
Krabbe disease is a progressive neurologic disorder caused by deficiency of the lysosomal enzyme galactocerebrosidase. The disease commonly has an early-infantile onset, but can have late-infantile, juvenile, or adult-onset phenotypes. Classic computed tomography (CT) and magnetic resonance imaging (MRI) findings in Krabbe have been well described. We report a patient, ultimately diagnosed with juvenile-onset Krabbe, who presented with atypical CT imaging and rapid disease progression. Our patient was a previously healthy and developmentally appropriate female who presented at 3 years 4 months of age with ataxia and motor regression that had progressed over the course of 6 weeks without an identifiable catalyst. CT, performed in the emergency setting, demonstrated extensive white matter hyperdensity. Subsequent MRI showed T2 hyperintensity of the white matter corresponding to the areas of hyperdensity on the CT, as well as enhancement of multiple cranial nerves bilaterally, suggestive of Krabbe disease. Enzymatic testing demonstrated low galactocerebrosidase activity and molecular testing of GALC revealed compound heterozygosity for 2 known pathogenic mutations, consistent with a diagnosis of Krabbe Disease. This included the common 30-kb deletion and a known pathogenic mutation associated with juvenile/adult-onset disease. Our patient's diffuse hyperdensity on CT offers a new radiographic finding to include in the repertoire of Krabbe imaging, and thus aide in the diagnostic evaluation. The rapidity of progression our patient demonstrated is additionally unique and should be considered in the identification of juvenile Krabbe as well as the complicated decision-making process regarding potential treatments.